Oedipus, the plague and the sphinx. Animal and human in one of the constituent myths of our subjectivity (Papeles, 2022)
This work intends to reread one of the founding myths of the West, together with some of its most famous interpretations, in light of the question about the modes of relationship between man and other living beings. For these purposes, Oedipus Rex, by Sophocles, is chosen for three interrelated reasons: 1) because of the undoubted importance of this work in the history of Western modeling and understanding of our psychic structure; 2) because in it, the discovery of the human depths takes place against the backdrop of a plague that devastates the city of Thebes, a characteristic that gives it a sinister relevance; 3) because of the peculiar meaning that the presence of animality acquires in this fantasy of human origins. This philosophical approach to one of the symbolic foundations of our culture aspires to contribute to the understanding and criticism of some presuppositions that consolidate germs of sovereign pretensions of self,sufficiency and human exceptionality, hinder and limit the scope of a possible dialogue, and distance the horizon of ecological justice.
Keywords: subjectivity; rights of nature; humanism; psychoanalysis; philosophy